Synthesis of hydroxyapatite crystals using carboxymethyl inulin for use as a delivery of ibuprofen - Oner, Mualla; Uysal, Umut (ELSEVIER SCIENCE BV, 2013)
In the present study biodegradable, environmentally friendly polysaccharide-based polycarboxylate, carboxymethyl inulin (CMI), was used to produce hydroxyapatite (HAP) particles by wet chemical synthesis under controlled temperature, pH, and atmospheric conditions. The morphology and microstructure of the HAP nanoparticles were investigated by XRD, SEM, DTA-TGA and FTIR. CMI affects morphology, surface area, dimension and particle size distribution of the crystals. The reduction in size is greater in the direction of the c-axis. The increase in the polymer concentration to 7.5 g/L resulted in the mixture of nanoparticles with particle sizes of less than 100 nm. The SEM micrograph shows the formation of well-crystallized, agglomerated small particles of HAP. X-ray analysis has Shown that the resulting particles have high thermal stability. The obtained crystals were used to produce tablets by direct compression of HAP. The influence of sample's CMI concentration on drug release profiles was investigated by using ibuprofen (C13H18O2) as a model drug. The model was used to determine the effective diffusion coefficient of the drug from the tablets. A good agreement between experimental data and model predictions was obtained as calculated in the present work. The values of the diffusion coefficients range from 1.62 x 10(-7) to 4.72 x 10(-7) m(2) h(-1). (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Hydroxyapatite; Nanomaterials; Biopolymers; Drug release; Ibuprofen; TAILOR-MADE INHIBITORS; DRUG-RELEASE; IN-VITRO; OXALATE CRYSTALLIZATION; CALCIUM-OXALATE; GROWTH; POLYELECTROLYTES; ARCHITECTURE; MORPHOLOGY; ACID; Materials Science